Store-operated calcium entry remains fully functional in aged mouse skeletal muscle despite a decline in STIM1 protein expression. - Edwards, Joshua N; Blackmore, DG; Gilbert, Daniel; Murphy, RM; Launikonis, Bradley S (Aging Cell, 2011)
Store-operated Ca(2+) entry (SOCE) is a robust mechanism in skeletal muscle, supported by abundant STIM1 and Orai1 in the junctional membranes. The precise role of SOCE in skeletal muscle Ca(2+) homeostasis and excitation-contraction coupling remains to be defined. Regardless, it remains important to determine whether the function and capacity of SOCE changes in aged skeletal muscle. We identified an approximate 40% decline in the expression of the integral SOCE protein, stromal interacting molecule 1 (STIM1), but no such decline in its coupling partner, Orai1, in muscle fibers from aged mice. To determine whether this changed aspects of SOCE functionality in skeletal muscle in aged mice, Ca(2+) in the cytoplasm and t-system were continuously and simultaneously imaged on a confocal microscope during sarcoplasmic reticulum Ca(2+) release and compared to experiments under identical conditions using muscle fibers from young mice. Normal activation, deactivation, Ca(2+) influx, and spatiotemporal characteristics of SOCE were found to persist in skeletal muscle from aged mice. Thus, SOCE remains a robust mechanism in aged skeletal muscle despite the decline in STIM1 protein expression, suggesting STIM1 is in excess in young skeletal muscle.